A LEARNING MODEL OF ISLAMIC RELIGIOUS EDUCATION FOR INSTILLING RELIGIOUS MODERATION VALUES IN A VOCATIONAL HIGH SCHOOL - Mardatillah, Mardatillah; Syahid, Ahmad; Rustina, Rustina; Anirah, Andi (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This article discusses a learning model of Islamic religious education for instilling religious moderation values at a vocational school. The research used a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The results show that the Islamic religious education learning models used by Islamic teachers in instilling the value of religious moderation at the vocational high school Palu are the Contextual Learning Model, Project Learning Model, and Group Learning Model. In the contextual learning model, the activities carried out by students are that the teacher gives assignments to students to read the topic of discussion that day, in this case, the values ​​of religious moderation, namely tolerance in terms of religion, ethnicity, race, and the prohibition of committing acts of violence, after that students connect it with real-life experienced by students. Implementation of the Islamic religious education learning model in instilling the value of religious moderation at the vocational high school in Palu as an effort to maintain diversity in the school within a frame of peace, tolerance, maintaining each other's feelings so as not to offend each other, especially regarding religion, giving freedom to each religion to celebrate their respective religious holidays both within the school environment and outside the school, providing good role models and advice and accustoming students to empathize with humanity by holding social service activities and other extra-curricular activities.